(untitled) (Bangladesh Journal of Microbiology, 2016)
The present study was aimed to develop an enzyme assisted dehairing method as an alternative and ecofriendly technique to reduce the use of harsh chemicals in leather manufacturing. For this purpose, two proteases namely alkaline protease (601 U/ml) and keratinase (132 U/ml) were produced by Bacillus licheniformis MZK05M9 (BlM9) in Soya molasses medium and Feather mill medium respectively, in 7.0 L bioreactor at pH 7.5 and 37°C. The cell free enzyme preparations were used together at 2.5% level in dehairing experiments. Three sets of experiments for dehairing of goat skins were performed with (1) enzymes; (2) enzymes and 5% lime (CaO) and (3) 2% sodium sulfide (Na2S) and 5% lime. The treatment with enzymes removed 85% of hair from goat skin after 24 hrs under mild shaking condition at room temperature where as the treatment with enzymes and 5% lime together resulted in 100% dehairing under similar conditions. Sodium sulfide along with lime also removed 100% hair faster (with 20 hrs) than other two treatments. The grain surface of the enzyme treated skin was smoother and silkier than that of the chemicals treatment as revealed by Scanning Electron Microscopy. Thus these results indicated that, the enzyme assisted method can be applied in largescale dehairing trial to reduce the use of harsh sodium sulfide. Bangladesh J Microbiol, Volume 32, Number 1-2,June-Dec 2015, pp 33-37